2011
DOI: 10.1016/j.visres.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Distractor-induced blindness for orientation changes and coherent motion

Abstract: The conscious perception of simple visual stimuli can be modulated by the presence of distractors. In the motion blindness paradigm, the detection of coherent motion is impaired when task-irrelevant motion distractors are presented prior to the target. Aim of this study was to examine the feature specificity of the distractor effect. For this reason, targets were either defined by motion coherence ("motion blindness") or orientation changes ("orientation blindness"). In a series of three experiments we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
30
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 22 publications
10
30
1
Order By: Relevance
“…The activation of the process shares the prerequisites of contingent attentional capture-as far as a match between the features of the distractor and the target is required. In line with our behavioral findings (Michael et al, 2011), the pattern of neural activity is independent of the visual feature defining the distractor. Similar ERP results have been obtained for orientation changes and for motion episodes (Niedeggen et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The activation of the process shares the prerequisites of contingent attentional capture-as far as a match between the features of the distractor and the target is required. In line with our behavioral findings (Michael et al, 2011), the pattern of neural activity is independent of the visual feature defining the distractor. Similar ERP results have been obtained for orientation changes and for motion episodes (Niedeggen et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Distractors in the motion task were defined as "incongruent distractors" because a different visual feature defined the target. On the basis of behavioral findings from our previous experiments on the effect of feature specificity (Michael, Hesselmann, Kiefer, & Niedeggen, 2011), a "mixed" distractor block was not included in the design: We have shown that the expression of distractor-induced blindness was not affected if incongruent features were added to RSVP sequences determined by congruent distractors (Experiment 3).…”
Section: Stimuli Task and Designmentioning
confidence: 99%
“…Previously, task-irrelevant stimuli were seen to reduce responses to task-relevant stimuli. That distractor inhibition [45], [46], [47] is smaller with complex stimuli and larger with demanding tasks [48], [49], [50]. Our selective attention task reverses that effect, with the 2 nd stimulus enhancing responses (Figure 2).…”
Section: Discussionmentioning
confidence: 66%
“…These results fit well with our proposal that access to consciousness is controlled by those BG pathways that modulate activity in the prefrontal cortex. Michael, Hesselmann, Kiefer, and Niedeggen (2011) recently showed that distractor-induced blindness works not only for motion stimuli but also for changes in the orientation of static stimuli. Our model readily embraces these results by assuming that different input stimuli stimulate the same BG pathways.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the model does not account for findings that the blindness effect increases in magnitude with increasing numbers of distractors (Hesselmann et al, 2006;Michael et al, 2011;Niedeggen et al, 2004Niedeggen et al, , 2012. Moreover, the current implementation of the reset pulse that terminates reverberation of activity in the closed frontal loop is of a rather abstract nature as it is evoked from outside the model rather than originating from model dynamics.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%